JUDI SEPAK BOLA ONLINE DI KALANGAN MAHASISWA UNIVERSITAS RIAU - Nuraga Sugiyarto Putra; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research conducted in the Bina Widya Street, Riau University‟s Campus, Panam, Pekanbaru City which aims to identify factors that encourage students to play online gambling . This study entitled "Online Gambling of Football Among Riau University Students' formulation of the problem in this research was to determine the factors that encourage students to play football gambling online. To find out how online football gambling impact on students. The skind of the research used in this research was descriptive qualitative research. Data collection was done by interview, observation and documentation. The tools used were interview guidelines. Mechanical for collecting respondents in this study was purposive sampling of respondents withdrawal based on certain criteria. These results indicate that the factors that encourage students to play football gambling online is the lack of control of the family, the benefits that may be obtained, situational, a willingness to try, the perception of a skills and add to the excitement in watching a match. With student participation in the game of football gambling online, they also feel the impact. These impacts include the following impact on student achievement, health impacts, the impact on the economy, as well as the impact on personality.Keywords: Football online gambling, Unisersity Students